Pengaruh Model Pembelajaran “Picture And Picture” Terhadap Kemampuan Menulis Teks Eksposisi Siswa Kelas VIII SMPIT Gema Insan Cendekia - Indah Nurwulandari; M. Januar Ibnu Adham; Ferina Melisanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims of this study were 1) To determine the effect of the Picture and Picture learning model on the ability to write Exposition texts for class VIII SMPIT Gema Insan Cendekia. 2) To find out the application of the Picture and Picture learning model to the ability to write Exposition texts for class VIII SMPIT Gema Insan Cendekia. The research method used in this research is the experimental method. Based on the results of research that has been carried out with a sample of 30 students in the experimental class and 30 students in the control class, it was found that there was an effect of using the picture and picture learning model on the ability to write expository text. This is evidenced by the results of the t-test calculations that have been carried out by researchers. The result of the t-test is tcount 5,800 with a significance level of 0.05, the value of ttable is 2,000.